2015
DOI: 10.1134/s0006297915060127
|View full text |Cite
|
Sign up to set email alerts
|

Effect of laser optoperforation of the zona pellucida on mouse embryo development in vitro

Abstract: The effect of laser optical perforation of the zona pellucida on the viability and development of mouse embryos has been studied. Operations of zona pellucida thinning and single or double perforation were carried out on 2-cell embryo, morula, and blastocyst stages with a laser pulse (wavelength 1.48 µm, pulse duration 2 ms). Embryo development up to the blastocyst stage and hatching efficiency were statistically analyzed. It was found that 2-cell or morula stage embryo zona pellucida thinning or single perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…This indicates the safety of laser device on assisted hatching. Zakharchenko et al reported that zona pellucida perforation by laser device at the blas-tocyst stage had a negative effect and that hatching did not occur after perforation of zona pellucida [18]. Therefore, we could assume that the safety or detrimental effect of laser device on blastocyst is dependent on the method of laser application.…”
Section: Discussionmentioning
confidence: 94%
“…This indicates the safety of laser device on assisted hatching. Zakharchenko et al reported that zona pellucida perforation by laser device at the blas-tocyst stage had a negative effect and that hatching did not occur after perforation of zona pellucida [18]. Therefore, we could assume that the safety or detrimental effect of laser device on blastocyst is dependent on the method of laser application.…”
Section: Discussionmentioning
confidence: 94%
“…The results of ZP drilling at blastocyst stage in locations close to either the TE or ICM have recently been reported [42][43][44][52][53][54][55][56] and are summarized in Table 3. As a rule, an infrared diode laser (λ = 1.48 μm) is used to create a hole.…”
Section: Discussionmentioning
confidence: 99%